2021
DOI: 10.1063/5.0054742
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral tilting dominated phase transition in compressed double perovskite Ba2SmBiO6

Abstract: The comprehension of structural behaviors in double perovskites is crucial for their functional optimization, especially when applying external regulations. Here, to inquire about potential structures with better magnetic performance, high-pressure phase transformation in double perovskite Ba 2 SmBiO 6 was first investigated up to 50 GPa via in situ high-pressure x-ray diffraction and Raman spectroscopy. A pressure-induced phase transition from cubic Fm-3m to orthorhombic Pnma is discovered at 4.8 GPa, accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…It has been established that, for ABO 3 oxides, presence or absence of a particular structural mode (or modes) is a determining factor to identify symmetry from Raman spectroscopy studies. For nanocrystalline LuFeO 3 orthoferrites, it has been observed that the wavenumber of the Raman mode Ag (3) increases with FeO 6 tilt angle, indicating that the Raman mode is sensitive to orthorhombic distortion. , The structural modes we found are consistent with experimental reports. In addition, presence of Q AFEO and Q T modes have been found experimentally for a layered ordered double perovskite, RBaMn 2 O 6 (R = Pr and Nd) . Antiferroelectric A-site displacement for A-site ordered phase has been reported for BaSrMWO 6 (M = Ni, Co, and Mg) with Raman spectroscopy .…”
Section: Resultssupporting
confidence: 89%
“…It has been established that, for ABO 3 oxides, presence or absence of a particular structural mode (or modes) is a determining factor to identify symmetry from Raman spectroscopy studies. For nanocrystalline LuFeO 3 orthoferrites, it has been observed that the wavenumber of the Raman mode Ag (3) increases with FeO 6 tilt angle, indicating that the Raman mode is sensitive to orthorhombic distortion. , The structural modes we found are consistent with experimental reports. In addition, presence of Q AFEO and Q T modes have been found experimentally for a layered ordered double perovskite, RBaMn 2 O 6 (R = Pr and Nd) . Antiferroelectric A-site displacement for A-site ordered phase has been reported for BaSrMWO 6 (M = Ni, Co, and Mg) with Raman spectroscopy .…”
Section: Resultssupporting
confidence: 89%
“…The phase-transition path of Ba 2 SmSbO 6 under compression is consistent with that of Ba 2 YTaO 6 . It is reported that Ba 2 SmBiO 6 experiences phase transition from cubic ( Fm- 3 m ) to orthorhombic ( Pnma ) at high pressure . Compared with Ba 2 SmSbO 6 , the p–d electron interaction in Ba 2 SmBiO 6 is stronger, leading to the lower crystal symmetry at high pressure.…”
Section: Resultssupporting
confidence: 71%
“…The Grüneisen parameters γ and a are positive in the Fm- 3 m structure below 24.0 GPa, due to the hardening of chemical bonding under compression. Compared with Ba 2 SmBiO 6 , the pressure coefficients of Ba 2 SmSbO 6 are larger, indicating that Ba 2 SmSbO 6 is easier to compress than Ba 2 SmBiO 6 . Furthermore, the Grüneisen parameter of Ba 2 SmSbO 6 is larger than Ba 2 SmBiO 6 , demonstrating that the Sb–O bond has a stronger ionic character than Bi–O under compression.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar behavior of Raman mode evolution with temperature was observed for other double perovskite oxides too. 81–83…”
Section: Resultsmentioning
confidence: 99%